(untitled) (The Journal of Psychology and Sociology, 2012)
In correctional work over child the parental the relations a big role today plays the triad structure of relationship in a triad the child – the parent – the teacher plays. The article offers training class for parents on the basis of the personal focused approach in studying of the child parental relations, and also methods of influence and correction of the child parental relations is offered. Article is intended for social teachers and school psychologists for carrying out psychocor- rectional methods of work.